Mediating effect of tacit knowledge sharing on the relationship between individual factors and innovative behaviour among nurses - Wah, Nur Constance (2019)
The purpose of this study is to the examine the mediating effect of tacit knowledge sharing on the relationship between several individual factors (trust, perceived supervisor support, supervisory justice, tie strength, and organisational behaviour) and innovative behaviour among nurses in a Malaysian public teaching hospital. Tacit knowledge sharing is crucial in teaching hospital because it placed more demand for training healthcare professionals in education, research, and innovative activities. This study attempts to determine the relationship between individual factors and innovative behaviour, and on tacit knowledge sharing, and to examine the influence of tacit knowledge sharing on innovative behaviour. It is the aims of this study to look at the mediating effect of tacit knowledge sharing on the relationship between individual factors and innovative behaviour. Using social exchange theory as the underpinning theory, sixteen hypotheses were tested. The research method included both self-report and supervisorreport both 360 nursing employees and 21 nurse supervisors in Universiti Kebangsaan Malaysia Medical Center (UKMMC) were selected using disproportionate stratified sampling, which yields 94.17 per cent response rate. Data were obtained through survey and analyses were performed using Structural Equation Modelling (SEM) confirmed using Partial Least Squares (PLS). The results showed that nine hypotheses were significant and two hypotheses were insignificant for direct effect. Moreover, tacit knowledge sharing played a mediating effect in trust, supervisory justice, tie strength and organisational citizenship behaviour in their relationship with innovative behaviour. Interestingly, perceived supervisor support does not matter for both tacit knowledge sharing and innovative behaviour. The findings conclude that workplace exchange relationship is crucial between nurse and supervisor. This study provides a conceptual basis for effective tacit knowledge sharing in a teaching hospital. From the practical aspect, this study underlines the importance of nurses to share tacit knowledge in order for them to be innovative.